`-3(y-3y)+4 =-4(3y-y)+6+13y`

Start by combining like terms inside the parentheses.

`-3(-2y) +4 = -4(2y) +6 +13y`

Multiply terms inside the parentheses by `-3` on the left side of the equation and `-4` on the right side of the equation.

`6y +4 = -8y +6 +13y`

Combine like terms on the right side of the equation.

`6y+4 = 5y +6`

Now subtract `5y` from both sides of the equation.

`1y +4 =6`

Subtract `4` from both sides of the equation.

`1y=2`

`y=2`

Check your solution by plugging your answer into the original equation.

`-3(2-3(2))+4 = -4(3(2)-2) +6 +13(2)`

`-3(-4) +4 = -4(4)+6+26`

`12+4=-16+6+26`

`16= -16+32`

`16=16` Check

**The solution is y=2.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.